QTL Mapping and Data Mining to Identify Genes Associated With the Sinorhizobium fredii HH103 T3SS Effector NopD in Soybean - Wang, Jinhui; Wang, Jieqi; Ma, Chao; Zhou, Ziqi; Yang, Decheng; Zheng, Junzan; Wang, Qi; Li, Huiwen; Zhou, Hongyang; Sun, Zhijun; Liu, Hanxi; Li, Jianyi; et al. (Frontiers in Plant Science, 2020)
In some legume–rhizobium symbioses, host specificity is influenced by rhizobial type III effectors-nodulation outer proteins (Nops). However, the genes encoding host proteins that interact with Nops remain unknown. In this study, we aimed to identify candidate soybean genes associated with NopD, one of the type III effectors of Sinorhizobium fredii HH103. The results showed that the expression pattern of NopD was analyzed in rhizobia induced by genistein. We also found NopD can be induced by TtsI, and NopD as a toxic effector can induce tobacco leaf death. In ten soybean germplasms, NopD played a positively effect on NN (nodule number) and NDW (nodule dry-weight) in nine germplasm, but not in Kenjian28. Significant phenotype of NN and NDW were identified between Dongnong594 and Charleston, Suinong14 and ZYD00006, respectively. To map the QTL associated with NopD, a recombinant inbred lines population (RIL) derived from the cross between Dongnong594 and Charleston, and chromosome segments substitution lines (CSSLs) derived from Suinong14 and ZYD00006 were used. Two overlapping conditional QTL associated with NopD on chromosome 19 were identified. Two candidate genes were identified in the confident region of QTL, we found that NopD could influence the expression of Glyma.19g068600 (FBD/LRR) and expression of Glyma.19g069200 (PP2C) after HH103 infection. Haplotype analysis showed that different types of Glyma.19g069200 haplotypes could cause significant nodule phenotypic differences, but Glyma.19g068600 (FBD/LRR) was not. These results suggest that NopD promotes S. fredii HH103 infection via directly or indirectly regulates Glyma.19g068600 and Glyma.19g069200 expression during the establishment of symbiosis between rhizobia and soybean plants.